2010
DOI: 10.2174/1874312901004010001
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean Fever: A Retrospective Clinical and Molecular Study in the East of Anatolia Region of Turkey

Abstract: Familial Mediterranean Fever (FMF) is an autoinflammatory periodic disorder. We aim to identify the distribution and the frequency of the Mediterranean Fever (MEFV) gene mutations in the east of Anatolia in Turkey and perform a genotype/phenotype correlation in the patients’ cohort. The study was carried out on 415 clinically diagnosed Turkish FMF patients and 103 healthy controls. The tested individuals were screened for the most common twelve MEFV mutations. The most important features were the predominance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
1
20
0
7
Order By: Relevance
“…In the previous studies from Turkey, the frequency of E148Q mutation was found to range between 1.36 and 30.8%. In agreement with our study, it was found as the second most commonly seen mutation in many studies from Turkey (Akin et al, 2010;Dogan et al, 2012;Etem, 2010;Gulec et al, 2012;Ozturk et al, 2008;Pasa et al, 2008;Solak et al, 2008;Ulgenalp, 2009), whereas it was found as the most commonly seen mutation in the study by Evliyaoglu et al (2009) and by Yesilada et al (2012), with allele frequencies of 30.8% and 10.38%, respectively. E148Q mutation was the third most commonly observed mutation in the study by Ceylan et al (2012) and by Dundar et al (2011) with the allele frequencies of 4.42 and 5.15%, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the previous studies from Turkey, the frequency of E148Q mutation was found to range between 1.36 and 30.8%. In agreement with our study, it was found as the second most commonly seen mutation in many studies from Turkey (Akin et al, 2010;Dogan et al, 2012;Etem, 2010;Gulec et al, 2012;Ozturk et al, 2008;Pasa et al, 2008;Solak et al, 2008;Ulgenalp, 2009), whereas it was found as the most commonly seen mutation in the study by Evliyaoglu et al (2009) and by Yesilada et al (2012), with allele frequencies of 30.8% and 10.38%, respectively. E148Q mutation was the third most commonly observed mutation in the study by Ceylan et al (2012) and by Dundar et al (2011) with the allele frequencies of 4.42 and 5.15%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Study Group, 2005;Yalcinkaya et al, 2000;Akin et al, 2010;Ceylan et al, 2012;Dogan et al, 2012;Etem, 2010;Pasa et al, 2008;Yilmaz et al, 2001). It is the most frequently seen mutation in populations where FMF is prevalent including Iranian Azerbaijani Turks (Bonyadi et al, 2009), Jews (Ben-Chetrit et al, 2000Dode et al, 2000), Arabs (Al-Alami et al, 2003;Ayesh et al, 2005;Belmahi et al, 2012;Gershoni-Baruch et al, 2001;Majeed et al, 2005;Mattit et al, 2006;Medlej-Hashim et al, 2000 and Armenians (Cazeneuve et al, 1999;Sarkisian et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent mutations (M680I, M694V, V726A, M694I and E148Q) are found in more than two-thirds of cases. Genotype-phenotype correlation, thoroughly studied over the past few years, suggests that mutations located within the mutational hotspots in codons 680 and 694 are associated with severe disease, early onset, high frequency of attacks, the necessity of a high dose of colchicine to control attacks, and frequent occurrence of amyloidosis in untreated cases (6).…”
Section: Introductionmentioning
confidence: 99%
“…Preterm yenidoğanlarda MPV değerinin yük-sek olması kanama riskinin azaltılması açısından yardımcı bir faktör olacaktır. Respiratuar distres sendromu (RDS), akut pankreatit, sepsis ve ailevi akdeniz ateşi gibi birçok hastalığın MPV ile ilişkisi araştı-rılmıştır [7][8][9][10]. MPV'nin diğer enflamasyon belirteçleri ile birlikte kullanılabilecek hızlı, pratik ve ek bir maliyet getirmeyen bir belirteç olduğu gösterilmiştir.…”
Section: Discussionunclassified